Breast cancer-associated venous thromboembolism: A case–control study. (August 2016) - Rebouças, Danilo; Costa, Maria; Thuler, Luiz; Garces, Alvaro; Aquino, Luciana; Bines, José
Abstract: Breast cancer is frequently associated with venous thromboembolism (VTE). VTE may result in significant morbidity, a substantial economic burden and even leads to patients' death. Risk factor identification and management of VTE in breast cancer patients remains poorly studied. We evaluated breast cancer patients' baseline and treatment characteristics in predicting VTE occurrence as well as its prognosis. We conducted a case–control study of all breast cancer patients with a VTE diagnosed between January 2007 and December 2011 at the Instituto Nacional de Câncer (INCA) in Brazil. Two hundred and twenty five patients developed VTE and were compared with 225 controls, in the 5-year study period. The bulk of the thrombotic events were unilateral (94.2%) VTEs of the lower extremity (78.7%), largely proximally located (78%). VTE occurred more often within the first 3 years after the diagnosis of cancer (66.2%), being more common in the first 6 months (21.8%). Significant predictors of developing VTE were age 50 years and over (OR 1.85, 95% CI: 1.16–2.95), PS equal to or above 3 (OR 2.01, 95% CI: 1.24–3.26), and the presence of a CVC (OR 2.56, 95% CI: 1.42–4.62). This large retrospective analysis of VTE in breast cancer patients confirms that most events occur early in the treatment course. The incidence of VTE was associated with patients' age, PS, and the presence of CVC. Prospective studies are needed to evaluate outpatient thromboprophylaxis for selected groups of patients. Highlights: Breast cancer is frequently associated with venous thromboembolism (VTE). Most events are unilateral VTE of the lower extremity and they tend to happen early in the treatment course. Increasing age, a lower performance status and the presence of a central venous catheter increase the risk of VTE. Prospective studies are needed to evaluate outpatient thromboprophylaxis for selected groups of patients.